Islam Washatiyah Perspective of Tafsir Ibn Kathir and Hamka in the Contemporary Era - Mhd. Abdul Hakim; Arifinsyah; Siti Ardianti (Getpress Management Journals, 2024)
This research aims to examine the understanding and interpretation of Wasathiyah Islam according to two mufassirs Ibn Katsir and Hamka, who have different scientific backgrounds and social contexts. Ibn Kathir, as a classical scholar, emphasizes the meaning of wasathiyah as an attitude of fairness and balance in being a witness for humanity, while Hamka, with his contextual approach, highlights the importance of balance between worldly life and ukhrawi in every aspect of Muslim life. The method used in this study is thematic (maudhū'ī) which then analyzes Qur'anic verses related to wasathiyah interpreted by the two scholars. The results of the study show that despite the differences in approaches, both agree that Wasathiyah Islam is the key to maintaining the integrity of the ummah, reducing extremism, and building a social life based on justice and wisdom. This research makes an academic and practical contribution in understanding the relevance of the wasathiyah concept in facing various challenges of modern life.